A interculturalidade no cinema: um estudo da legendagem e da dublagem brasileiras em um filme francês contemporâneo - Sousa, Aída Carla Rangel de (2008)
In this research we present a study of cultural aspects in dubbed and subtitled films. As a case study, we chose to compare the original French version of "Le fabuleux destin d'Amelie Poulain" with both the subtitled and the dubbed versions in Portuguese, with focus on the interaction between the French and the Brazilian cultures. First we considered that (i) the translation process interferes on the perception of cultural relationships; and that (ii) dubbing and subtitling are two methods of translation that result in distinct perceptions from the spectator. Then, we adopted the translation interpretative theory (Seleskovicth; Lederer, 2001; Deslile, 1980) as the general theoretical framework, since it emphasizes the extralinguistic equivalence on the translation process. Furthermore, we based this research on three analytical procedures, which are: the four-step translating operation, the contrastive perception and a translation's typology based on Vinay and Dalbernet's linguistic procedures (Srpová, 1991, 1995, 2004). We extracted forty-six culture-related elements from the film and identified those belonging to the French ethno-universe. Then, the elements were classified with respect to a theoretical typology, based on concepts found in the Ethnography of Communication and a general typology, based on five general thematic groups, defined by the corpus. The results showed that both Brazilian versions tend to preserve those culture-related elements by using lexical loan and literal translation. The visual context, in its association with the linguistic procedures in both Brazilian versions, was also observed as an important element to the comprehension of the culture-related elements as they are considered in the French culture. As a general observation, the perception of culture-related elements in the film seems effectively be oriented by the translation methods